High Sensitive C-Reactive Protein And Apolipoprotein B Levels In Polycystic Ovary Syndrome - V.M.VINODHINI; V.DEVISRI; W.EBENEZER WILLIAM; M.MUTHULAKSHMI; ANJALAKSHI CHANDRASEKAR; S. GNANASAMBANDAM (International Journal of Pharma and Bio Sciences, 2012)
Polycystic ovary syndrome [PCOS] is associated with abdominal obesity, insulin resistance and dyslipidemia. Women with PCOS may be at an increased risk for the development of type 2 diabetes mellitus. Atherosclerosis is characterised by an inflammatory response of the arterial wall due to endothelial injury. Hence low grade chronic inflammation may independently predict coronary heart disease [CHD]. Serum high sensitive C-reactive protein [hsCRP], a marker of chronic subclinical inflammation which is actively involved in atherogenesis is considered a predictor of future CVD. We investigated hsCRP and apolipoprotein B [apoB] levels in a small population of 30 women with PCOS and 30 control subjects. In women with PCOS the levels of hs-CRP, apolipoprotein B and waist-to-hip ratio were significantly elevated when compared with controls. Screening with hsCRP and apolipoprotein B may provide a better risk assessment in patients with PCOS.